Occupational Health Problems: An Assessment of the Cardiovascular Health Status of Road Construction Workers in Imo State, Nigeria - Bwala, John Mark; Amadi, Agwu Nkwa; Iwuala, Chimezie Christian; Enebeli, Ugo Uwadiako (European Scientific Journal, ESJ, 2025)
Aims and Scope: Road construction work is uniquely demanding and highly stressful, which may impact the cardiovascular system, and this study assessed the cardiovascular health status of road construction workers in Imo State, Nigeria, focusing on blood pressure (BP) and pulse rate (PR). Methods: A cross-sectional descriptive design was employed, using a multi-stage sampling technique from different construction sites across the 3 senatorial zones of Imo State to collect data from 353 male road construction workers through structured questionnaires and physical assessments (BP and PR measurements). Data were analyzed using descriptive statistics, including frequency distributions for categorical variables (e.g., prevalence of hypertension and tachycardia) and summary statistics such as means and standard deviations for continuous variables (e.g., BP and PR). Results: The results indicated that 23.2% of participants had systolic hypertension, 48.4% had high-normal systolic blood pressure (SBP), and only 28.3% had optimal and normal SBP. Also, 9.9% had diastolic hypertension, 19.8% had high-normal diastolic blood pressure (DBP), and 70% had optimal and normal DBP. The differences across the classes of BP were statistically significant, p<0.001. Also, 6.2% participants exhibited tachycardia, and the differences in the occurrence of diastolic hypertension and tachycardia across the senatorial zones were not statistically significant (p=0.11 and 0.45, respectively). Additionally, 76.2% of the workers lacked regular medical check-ups, and only 29.2% consistently used personal protective equipment (PPE). Conclusions: These findings underscore the significant cardiovascular health risks faced by road construction workers, exacerbated by limited access to healthcare and occupational safety measures. The findings highlight the need for improved occupational health policy enforcement, health education, routine screenings, and worksite health interventions.